Early evidence for a stable and flexible foraging niche in the evolution of Homo - Frances Forrest; Eimy Gonzalez-Alvarez; Dan Palcu Rolier; Sharon Kuo; Matthew Skinner; Jonathan Reeves; Erin DiMaggio; Sarah Hlubik; Sahleselasie Melaku; Mathilde Ribordy; Alemu Gebresilassie Wolde; Emmanuel Ndiema; et al. (Proceedings of the National Academy of Sciences, 2026)
Major evolutionary transitions in Homo (e.g., increased brain size, complex social behavior) are linked to reliance on high-quality foods. Increased meat consumption likely contributed to this shift, but whether hominins practiced carcass acquisition and processing strategies consistently across time and environments remains unclear. The Koobi Fora Formation spans much of the Plio-Pleistocene and is central to reconstructing the ecology of early Homo . However, zooarchaeological research has focused almost entirely on the Okote Member (~1.56 to 1.38 Ma), while the KBS Member (~1.87 to 1.56 Ma) has yielded important hominin fossils but relatively few faunal assemblages comparably well preserved for similar analysis. We present an analysis of FwJj 80 (~1.6 Ma), an assemblage from the KBS Member that preserves butchered fauna associated with early Homo fossils. Results show that behaviors documented in the Okote Member, including early access to carcasses, selective transport of limbs, and systematic marrow extraction within riparian settings, were also practiced at FwJj 80. This provides the most comprehensive and systematically analyzed evidence of such behaviors within the KBS Member, demonstrating continuity in carcass-exploitation patterns between the KBS and Okote Members. Comparisons with FLK Zinj (~1.84 Ma, Tanzania) and Kanjera South (~2.0 Ma, Kenya) demonstrate a consistent foraging niche sustained across varied environmental contexts, underscoring behavioral flexibility as central to early Homo’ s evolutionary success.